Traditional Nature Management Areas as Means of Organizing the Economic Activities of the Siberian Arctic's Indigenous Minorities - Koptseva, Natalia P.; Kirko, Vladimir I.; Nevzorov, Viktor N.; Razumovskaya, Veronika A.; Bukharova, Eugenia B.; Semenova, Anna R. (International Review of Management and Marketing, 2016)
Since 2010, researchers have inhabited indigenous settlements, conducting field studies on the ways of preserving indigenous peoples' unique economic, environmental and cultural practices. The processes of new industrial reclamation of the Siberian Arctic have a direct effect on the area's indigenous populations living in the Arctic zone, including the Turukhan Area and Taymyr's Dolgano-Nenets Municipal District within the Krasnoyarsk Krai. In this area, traditional economic activities are practiced by the Nenets, the Evenks, the Evens, the Nganasans, the Dolgans, and the Selkups. The majority of experts believe that creating traditional nature management areas with a proper legal underpinning will enable a shift from the policy of state paternalism to the policy of strategic partnership between indigenous peoples and large financial and industrial groups, with state and local authorities assuming the role of mediators and guarantors. The Krasnoyarsk Krai is currently in the process of building a legal foundation for the creation of traditional nature management areas locally, which may make it possible to implement the ethnocultural standards of improving the quality of living for the Siberian Arctic's indigenous minorities. Keywords: Siberian Arctic, traditional economics, regional development JEL Classifications: R1, R5, Z1